“Janganlah Kamu Disebut Rabi”: Sebuah Pendekatan Hermeneutika Pedagogis terhadap Matius 23:8 - Saragih, Erman Sepniagus; Marbun, Benyamin; Sinaga, Veronika (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2024)
Matthew 23:8 is a complex and controversial passage. However, a comparison of Jesus' teaching principles and those of the Jewish rabbis that are widespread in the texts of Matthew can be useful to interpret the meaning of the verse in its broader context. Ignoring the duty to teach the scribes and Pharisees in Matthew 23:8 may result in a distortion of interpretation, even misrepresenting the meaning of the text. This paper provides a new perspective on the reading of Jesus’ prohibition “do not be called Rabbi” in Matthew 23:8 by using a hermeneutic-pedagogical approach. The purpose of this study is to understand and articulate why Jesus forbade the disciples and the people to be called rabbis and how this is read through a pedagogical lens. The results of this study are, first, there is a diacognition of the meaning of the word rabbi in Jesus’ teachings. Second, teaching does not lead to the goal of position and prestige. Third, Jesus was teaching a principle that prioritizes the attitude of brotherhood that serves each other with the view that Jesus is the only “Teacher.”